Relic populations of Fukomys mole-rats in Tanzania: description of two new species F. livingstoni sp. nov. and F. hanangensis sp. nov. - Faulkes,Chris G.; Mgode,Georgies F.; Archer,Elizabeth K.; Bennett,Nigel C. (PeerJ, 2017)
Previous studies of African mole-rats of the genera Heliophobius and Fukomys (Bathyergidae) in the regions of East and south central Africa have revealed a diversity of species and vicariant populations, with patterns of distribution having been influenced by the geological process of rifting and changing patterns of drainage of major river systems. This has resulted in most of the extant members of the genus Fukomys being distributed west of the main Rift Valley. However, a small number of isolated populations are known to occur east of the African Rift Valley in Tanzania, where Heliophobius is the most common bathyergid rodent. We conducted morphological, craniometric and phylogenetic analysis of mitochondrial cytochrome b (cyt b) sequences of two allopatric populations of Tanzanian mole-rats (genus Fukomys) at Ujiji and around Mount Hanang, in comparison with both geographically adjacent and more distant populations of Fukomys. Our results reveal two distinct evolutionary lineages, forming clades that constitute previously unnamed species. Here, we formally describe and designate these new species F. livingstoni and F. hanangensis respectively. Molecular clock-based estimates of divergence times, together with maximum likelihood inference of biogeographic range evolution, offers strong support for the hypothesis that vicariance in the Western Rift Valley and the drainage patterns of major river systems has subdivided populations of mole-rats. More recent climatic changes and tectonic activity in the “Mbeya triple junction” and Rungwe volcanic province between Lakes Rukwa and Nyasa have played a role in further isolation of these extra-limital populations of Fukomys in Tanzania.
Keywords: Fukomys; Mitochondrial DNA; African mole-rats; Rift Valley; Phylogeography; Bathyergidae; New species